2021
DOI: 10.1055/s-0041-1730346
|View full text |Cite
|
Sign up to set email alerts
|

Hemostasis and Fibrinolysis following Aneurysmal Subarachnoid Hemorrhage: A Systematic Review on Additional Knowledge from Dynamic Assays and Potential Treatment Targets

Abstract: Mortality after aneurysmal subarachnoid hemorrhage (aSAH) is augmented by rebleeding and delayed cerebral ischemia (DCI). A range of assays evaluating the dynamic process of blood coagulation, from activation of clotting factors to fibrinolysis, has emerged and a comprehensive review of hemostasis and fibrinolysis following aSAH may reveal targets of treatment. We conducted a systematic review of existing literature assessing coagulation and fibrinolysis following aSAH, but prior to treatment. PubMed, Embase, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 93 publications
(406 reference statements)
0
7
0
Order By: Relevance
“…Rebleeding is the most feared complication after SAH as it carries a high mortality [ 23 ]. The role of TXA in clot stabilization and its antifibrinolytic properties initially nurtured the idea of using it in SAH, and the results of various clinical trials supported it as well [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rebleeding is the most feared complication after SAH as it carries a high mortality [ 23 ]. The role of TXA in clot stabilization and its antifibrinolytic properties initially nurtured the idea of using it in SAH, and the results of various clinical trials supported it as well [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, while TXA may have some role in clot stabilization (especially when used long-term), there is little to no evidence to support its use at present. Recent studies have also suggested exploring alternative agents such as desmopressin to prevent rebleeding [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The last review of this section is written by the co-editors Hvas and Hvas and is a systematic review on hemostasis and fibrinolysis following subarachnoid hemorrhage. 12 Rebleeding and delayed cerebral ischemia increase mortality after subarachnoid hemorrhage, and hemostatic or antifibrinolytic therapy has not been able to decrease mortality. Gathering current knowledge on changes in hemostasis and fibrinolysis, evaluated by both conventional, quantitative, and dynamic assays may reveal potential treatment targets.…”
Section: Intracerebral and Subarachnoid Hemorrhagementioning
confidence: 99%
“…10 11 A high incidence of changes in coagulation and fibrinolysis has been reported following SAH involving both primary and secondary hemostasis. 12 Measurements of increased platelet-activating factors and a hypercoagulable state with increased coagulation factors and von Willebrand factor suggest the presence of a systemically disturbed coagulation system. 13 14 15…”
mentioning
confidence: 99%
“…10,11 A high incidence of changes in coagulation and fibrinolysis has been reported following SAH involving both primary and secondary hemostasis. 12 Measurements of increased platelet-activating factors and a hypercoagulable state with increased coagulation factors and von Willebrand factor suggest the presence of a systemically disturbed coagulation system. [13][14][15] Development of spontaneous ICH is closely linked to the presence of hypertension and constitutes 10 to 15% of annual 700,000 strokes in the United States, 16 with an ICH incidence of 12 to 15 cases per 100,000.…”
mentioning
confidence: 99%